An analysis of Japan’s English as medium of instruction initiatives within higher education: the gap between meso-level policy and micro-level practice - Aizawa, I; Rose, H (Springer Nature, 2018)
In 2014, Japan’s Ministry of Education (MEXT) announced the Top Global University Project (TGUP), a large-investment initiative to internationalise higher education that implicitly signalled increased emphasis on English-medium instruction (EMI) at Japanese universities. Despite substantial funding behind the initiative, little research has evaluated the implications for language planning, including contextualised implementation challenges. This study aims to investigate how the policy is being enacted into practice at a university in Japan at two different policy levels: the meso (institutional) and micro (classroom) level. The study contrasts one university’s TGUP meso-level policy documentation with data from semi-structured interviews with students and teachers to illuminate micro-level challenges. Data were coded according to emergent themes via qualitative text analysis, following similar processes to research into TGUP policy. The findings suggest that the meso-level policy goals of the university do not trickle down to micro-level practice as envisioned, revealing underlying challenges arising from policy diffusion. In comparing our results with data from other TGUP university studies, we conclude that micro-level linguistic challenges for teachers and students has relevance for other universities where English-taught programmes are being expanded via national and university-level policies.